2012
DOI: 10.3390/ijerph9020632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BMI Derived from Parent-Reported Height and Weight with Measured Values: Results from the German KiGGS Study

Abstract: The use of parent-reported height and weight is a cost-efficient instrument to assess the prevalence of children’s weight status in large-scale surveys. This study aimed to examine the accuracy of BMI derived from parent-reported height and weight and to identify potential predictors of the validity of BMI derived from parent-reported data. A subsample of children aged 2–17 years (n = 9,187) was taken from the 2003–2006 cross-sectional German KiGGS study. Parent-reported and measured height and weight were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 23 publications
4
26
3
2
Order By: Relevance
“…[13][14][15][16] The association between objective and subjective measures of weight, height, and BMI was strong, which is consistent with findings from some previous studies. 16,17 Besides, as in other studies, 13,16,[18][19][20][21][22] underestimation of weight and height based on subjective data was observed. In the present study, this underestimation can be considered small, as mean differences of less than 1 kg for weight and of less than 1 cm for height were observed for children.…”
Section: Discussionmentioning
confidence: 51%
“…[13][14][15][16] The association between objective and subjective measures of weight, height, and BMI was strong, which is consistent with findings from some previous studies. 16,17 Besides, as in other studies, 13,16,[18][19][20][21][22] underestimation of weight and height based on subjective data was observed. In the present study, this underestimation can be considered small, as mean differences of less than 1 kg for weight and of less than 1 cm for height were observed for children.…”
Section: Discussionmentioning
confidence: 51%
“…The validity of parent-reported height and weight in children varies across countries. A German study reported that parental reports of their children's BMI were underestimated and sensitivity and specificity for overweight ranged from 66.7% to 67.1% and from 90.1 to 91.2%, respectively, for boys and girls (35). However, a Japanese study suggests that parent-reported BMI is more precise; the correlations between parent-reported and measured BMI ranged between 0.86 and 0.97, and sensitivity and specificity for the presence of obesity ranged from 83.3% to 93.3% and 96.3% to 98.9%, respectively (36).…”
Section: Discussionmentioning
confidence: 99%
“…Brettschneider et al 13 observaron que en los niños mayores y en los adolescentes la proporción de sobrepeso y obesidad es subestimada por los padres. Del mismo modo, cuando son los jóvenes quienes informan de su peso y altura tienden a subestimar el primero y sobreestimar la segunda 15 .…”
Section: Discussionunclassified
“…Se trata del modo de obtener el registro del peso y la altura de los niños. En este sentido, se ha observado que cuando los datos son proporcionados por los padres de los niños y adolescentes, estos tienden infravalorar su peso y sobrevalorar su altura 13 .…”
Section: Introductionunclassified